No More Laissez Faire? Expert Evidence, Rule Changes and Reliability: Can More Effective Training for the Bar and Judiciary Prevent Miscarriages of Justice?. (October 2016) - Davies, Gemma; Piasecki, Emma
The apparent link between miscarriages of justice in prosecutions involving expert evidence and the level of training provided to the legal profession (the Bar in particular) and the judiciary in respect of such evidence was highlighted in 2005 with the publication of the House of Commons Science and Technology Committee Report Expert Evidence on Trial . 2 The Law Commission, in the 2011 Report Expert Evidence in England and Wales 3 subsequently comprehensively addressed the same issue. This article seeks to consider why appropriate training in relation to expert evidence is so necessary and questions whether, in the context of the amendments to what is now Part 19 of the Criminal Procedure Rules (CrimPR19) and Part 19A of the Criminal Practice Direction (CrimPD19A), there have been sufficient developments in training to effect a cultural change within the legal profession and ultimately substantially reduce the risk of future miscarriages of justice. Finally, the article debates the nature of required training, arguing that much more detailed training is required than has previously been considered and addresses where this training best sits.